Measuring and analysing inequality in the Distribution of Economic Welfare in Suleimania Governorate during (2007): - عثمان صابر ثيرداود; حمة شظان جمال (Journal of Economics and Administrative Sciences, 2013)
Abstract The issue of inequality in distribution of income and / or consumption expenditure is related to economic welfare because there is an inverse relationship between the economic welfare on the one hand, and the degree of inequality, on the other hand. Despite the fact that inequality is considered as normal phenomenon in every society, but if it exceeded certain limits it will lead to undesirable economic, social and political consequences. Therefore, the availability of indicators about inequality is a necessary tool for planning and evaluation of economic development programs. So, current study is aiming at measuring and analyzing the degree of inequality in distribution of consumption expenditure within three geographic areas of Suleimania governorate, namely: the governorate center, other urban and rural area, using familiar objective measures like Gini Cofficient, Kuznets Cefficient, and Coefficient of Variation, sa well as measuring and testing inequality between them by using special measures called Economic Distance Ratios. As was expected, the study found that the degree of inequality in per capita expenditure distribution is relatively high in the areas under consideration, as well as found significant differences between them.The data wich have been used were collected by Iraqi Central Bureau of Statistics and Information Technology cooperation with the statistics of the Kurdistan Region - Iraq during (2007).Finally,the study suggested some proposals that may serve future studies related to inequality, or that assist in designing of programs that contract the living standards gap between individuls of the society.